Oil-Type Sunflower Cost-Return Budget in North Central and Northeast Kansas - O'Brien, Daniel M.; Duncan, Stewart R.; Dhuyvetter, Kevin C. (My University, 2014)
This publication provides estimated cost and returns for forward farm planning for producing sunflowers in north central and northeastern Kansas.
MF2144_2014_02
Keywords: MF2144; Crops; Economics; MF